Evaluation of the effect of apixaban on the primary intact intervertebral disc cell cultures (Annals of Medical Research, 2021)
Aim: Apixaban is a frequently preferred pharmacological agent in clinics to prevent deep vein thrombosis and pulmonary embolism. Such new oral anticoagulants may cause hemorrhage’s in tissues and/or organs or may cause gastrointestinal symptoms without bleeding. It is also reported in the literature that it may lead to mental disorders, unwanted disorders in the urinary tract and skeletal-muscle system. However, when the literature is examined, there are no studies, which are of high-evidential value, evaluating the efficacy of apixaban on healthy, intact intervertebral disc tissue, and matrix-like structures. In this pharmaco-molecular study, it was aimed to investigate the effects of a new oral anticoagulant agent containing the active ingredient apixaban on the intact intervertebral disc tissue cells, extracellular matrix (ECM) structure and to evaluate its positive and / or negative effects on gene expressions of cartilage oligo matrix protein (COMP), chondroadherin (CHAD), and Matrix Metalloproteinase (MMP)s.Material and Methods: The primary cell cultures were prepared from the intact tissues of the patients with the traumatic intervertebral disc herniation. Apixaban was administered to the cultures and molecular analyses were performed for 21 days. The data obtained from the apixaban-administered and non-apixaban-administered samples were evaluated statistically and the significance value was accepted as P 0.05.Results: The changes were observed in the cell proliferation and the expressions of the mentioned genes in the apixaban-administered group. The suppression of COMP value and the increase in MMP-13 value may be indicative of the development of matrix degeneration in the apixaban-administered group, compared to the non-drug-administered control group. Conclusion: The selectivity is one of the most important features of the drugs. However, it should not be forgotten that no drug will only produce the desired effect.